Measuring English language workplace proficiency across subgroups: Using CFA models to validate test score interpretation. (January 2017) - Yoo, Hanwook; Manna, Venessa F.
This study assessed the factor structure of the Test of English for International Communication (TOEIC ® ) Listening and Reading test, and its invariance across subgroups of test-takers. The subgroups were defined by (a) gender, (b) age, (c) employment status, (d) time spent studying English, and (e) having lived in a country where English is the main language. The study results indicated that a correlated two-factor model corresponding to the two language abilities of listening and reading best accounted for the factor structure of the test. In addition, the underlying construct had the same structure across the test-taker subgroups studied. There were, however, significant differences in the means of the latent construct across the subgroups. This study provides empirical support for the current score reporting practice for the TOEIC test, suggests that the test scores have the same meaning across studied test-taker subgroups, and identifies possible test-taker background characteristics that affect English language abilities as measured by the TOEIC test.